2012
DOI: 10.1103/physrevlett.108.115502
|View full text |Cite
|
Sign up to set email alerts
|

All-Electron Path Integral Monte Carlo Simulations of Warm Dense Matter: Application to Water and Carbon Plasmas

Abstract: We develop an all-electron path integral Monte Carlo method with free-particle nodes for warm dense matter and apply it to water and carbon plasmas. We thereby extend path integral Monte Carlo studies beyond hydrogen and helium to elements with core electrons. Path integral Monte Carlo results for pressures, internal energies, and pair-correlation functions compare well with density functional theory molecular dynamics calculations at temperatures of (2.5-7.5)×10(5) K, and both methods together form a coherent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
149
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(152 citation statements)
references
References 27 publications
3
149
0
Order By: Relevance
“…In order to minimize finite-size errors, the total energy was converged to better than 0.2% for a 24 atom cubic cell. Though this may seem like a small number of atoms, we stress that the number of atoms/cell needed to accurately compute energy and pressure decreases rapidly for condensed systems as T is increased into the plasma regime [14,34,51].…”
Section: B Pimc Calculationsmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to minimize finite-size errors, the total energy was converged to better than 0.2% for a 24 atom cubic cell. Though this may seem like a small number of atoms, we stress that the number of atoms/cell needed to accurately compute energy and pressure decreases rapidly for condensed systems as T is increased into the plasma regime [14,34,51].…”
Section: B Pimc Calculationsmentioning
confidence: 99%
“…In this approach, unlike in typical implementations of DFT, there is no mean-field assumption made for the many-electron problem, and the imaginary time treatment makes high-T simulations more efficient to perform than low-T simulations. Although assumptions regarding the nodal surface of the many electron density matrix necessarily introduce approximations for the treatment of atomic shells, it is very encouraging that recent work on the C plasma has demonstrated that EOS predictions can be made with this method which smoothly interpolate between DFT-MD results at the lower temperatures and the high-T Debye-Hückel limit [14].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations